(untitled) (Journal of Parents and Teachers, 2013)
This article called Gospel, whose name was chosen because of the musical style, is the eighteenth article of the series “Music and more Music”. It consists on a brief explanation of this style focusing on its history, social context, musical characteristics and the topics that are more likely to appear. After the introduction, the author proposes a song to work in the classroom by doing an analysis of the lyrics and the music. At the end, there are various activities related to the song that are orientated to work different values in the class. The song that was chosen in this article it is called “This little light of mine” by Bruce Springsteen. The values that can be found in this song are freedom, creativity, self-esteem and spirituality.